1987
DOI: 10.1161/01.cir.76.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heart rate on ventricular size, stroke volume, and output in the normal human fetus: a prospective Doppler echocardiographic study.

Abstract: The effect of heart rate on cardiac output in the fetal heart is controversial. We used Doppler echocardiography to investigate the effects of increasing heart rate on stroke volume and ventricular output in the normal human fetal heart. Heart rate was increased in 25 human fetuses (mean age 36 weeks) by auditory stimulation with a sound emitter placed on the mother's abdomen. Aortic or pulmonary diameters were measured at valve level from two-dimensional echocardiographic images and cross-sectional areas were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(30 citation statements)
references
References 25 publications
0
26
0
2
Order By: Relevance
“…However, their magnitudes strongly depend on RRI. Lower RRI is associated with lower ventricular preload, which, mediated by the Frank-Starling mechanism, results in reduced SV (48). Consequently, the lower SV and LVET in FMS patients could be explained by their low RRI.…”
Section: G a Reyes Del Paso Et Almentioning
confidence: 99%
“…However, their magnitudes strongly depend on RRI. Lower RRI is associated with lower ventricular preload, which, mediated by the Frank-Starling mechanism, results in reduced SV (48). Consequently, the lower SV and LVET in FMS patients could be explained by their low RRI.…”
Section: G a Reyes Del Paso Et Almentioning
confidence: 99%
“…In adults, the Frank-Starling mechanism refers to the direct influence of end-diastolic volume on stroke volume; the intrinsic length-tension relationship of increasing cardiac muscle length by increasing end-diastolic volume will increase contractile force and therefore increase stroke volume. Some fetal studies have demonstrated that heart rate is the major determinant of fetal cardiac output rather than stroke volume [4648]. These studies found that increasing preload as a means of increasing stroke volume via blood or saline infusion had little effect on cardiac output [47].…”
Section: Ventricular Output and Myocardial Dysfunctionmentioning
confidence: 99%
“…8 ' 9 In later investigations, however, Kenny and collaborators showed, using echo-Doppler technology, that variations in fetal heart rate were not necessarily associated with alterations in cardiac output. 10 Without delving into too many details, the following comments can be made on this controversial aspect of fetal myocardial function (Table 1). First, one must remember that the Frank-Starling relationship has been demonstrated in the isolated myocardium of the fetal heart.…”
Section: Effect Of Changes In Loading Condition On the Fetal Myocardiummentioning
confidence: 99%
“…45 while placental vascular impedance does not change during the same period. 10 This could decrease the amount of forward flow through the isthmus and create a growth discrepancy between this vascular segment and the adjacent arteries.…”
Section: The Aortic Isthmusmentioning
confidence: 99%